1998
DOI: 10.1002/(sici)1097-0266(1998110)19:11<1007::aid-smj999>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Governance and uncertainty: the trade-off between administrative control and commitment

Abstract: This study elaborates upon the motives for initiating equity‐based collaborations vs. acquisition of another firm already having a desired technology. We characterize both minority direct investments and joint ventures as options to defer either internal development or acquisition of a target firm. In domains where learning about growth opportunities dominates investment activity, this incremental mode of governance economizes on the cost of committing resources to a technology with an uncertain value. Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
248
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(266 citation statements)
references
References 61 publications
14
248
1
3
Order By: Relevance
“…These results are consistent with prior research that emphasizes the real options perspective (Folta, 1998) or the coordination or knowledge perspective (Gulati & Singh, 1998) on ownership, respectively. We also found that industry effects were significant, suggesting that ownership choices in inter-firm relationships vary systematically across industries.…”
Section: Results For the Control Variablessupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with prior research that emphasizes the real options perspective (Folta, 1998) or the coordination or knowledge perspective (Gulati & Singh, 1998) on ownership, respectively. We also found that industry effects were significant, suggesting that ownership choices in inter-firm relationships vary systematically across industries.…”
Section: Results For the Control Variablessupporting
confidence: 91%
“…The real options perspective suggests that when there is significant uncertainty about the value of a partner's resources, then taking equity ownership in the partner may prematurely increase the opportunity cost of commitment for the focal firm (Folta, 1998). In order to distinguish it from demand uncertainty, we included information on technological uncertainty via the item "Extent to which we understand, and can assess, the relative benefits and viability of the technology being accessed."…”
Section: Control Variablesmentioning
confidence: 99%
“…In addition, new entrants may be further motivated to cooperate with incumbents as alliances with established firms can bestow legitimacy, and thus positive reputational effects (Stuart, Hoang, and Hybels, 1999). Incumbents, on the other hand, often prefer cooperative arrangements over the acquisition of new entrants in order to internalize the new technology and thus maximize the value of their real options, particularly in environments of high uncertainty (Folta, 1998). Williamson (1985) has pointed out that extensive cooperation between incumbent and new entrant firms may ensue in the context described above.…”
Section: Strategic Alliances and New Product Developmentmentioning
confidence: 99%
“…Although it can be regarded as a part of environmental munificence, according to the managers size has a strong effect on strategic decisions and should be considered separately. [4]; [29]; [30]; [31]; [27]; [32]; [33] Environmental munificence (C12) [4]; [30]; [27]; [34]; [28]; [34]; [33]; [35] Industry size (C13) [27] 2.1.…”
Section: Industry Sizementioning
confidence: 99%
“…Depending on the strategy, greater cultural distance can have two controversial affects; it can either improve the learning mechanism Folta and Ferrier [43] or can create compatibility problems ( [44]). Partners' similarity (C41) [33]; [30] Prior relations (C42) [41]; [42] Relatedness(C43) [31]; [32] Cultural distance (C44) [43]; [40] The relevant factors that affect the strategy selection decision are defined based on the literature review and a hierarchical model for strategic decision selection has been conducted ( Figure 1). The model is modified by tree experts on this field, these experts are academicians and their working field of interest is strategic management.…”
Section: Cultural Distancementioning
confidence: 99%